Careers - from Dilbert to Da Vinci. - Karlin, S. (IEEE spectrum)
This paper discusses how companies find new ways to harness their engineer's creativity. There are several ways on improving their creativity and originality in their field of work. One way is companies can get around this issue is to rotate engineers through different jobs, which exposes them to a broader range of ideas and perspectives. Companies are also finding that giving engineers more autonomy and percolation time stimulates their creativeness. Incentives should also support the work's importance.